THE APPLICATION 0F LEARNING MODELS OF NUMBERED HEAD TOGETHER (NHT) ON THE SUBJECTS OF ELECTRICAL LIGHT VEHICLE MAINTENANCE COMPETENCY IN UNDERSTANDING THE STARTER SYSTEM IN CLASS XI LIGHT VEHICLE ENGINEERING PROGRAM (TKR) OF SMKN-1 SANAMAN MANTIKEI - Dewik; Wiyogo (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2020)
This research aims to know the student learning outcomes by applying the learning model of Numbered Head Together (NHT) on the subject of starter system in class XI TKR B under Light Vehicle Engineering competency in SMKN-1 Sananaman Mantikei Tumbang Manggu. The methods used in this research is a method of descriptive, with the population sample of research using students in Class XI TKR B SMK-1 Sanaman Mantikei Tumbang Manggu about 28 students. The instruments are based on the student activity sheet observations, data test results, and learning student response sheet. The research results show that the application of this learning model can improve the students’ learning response being more active than before to interact to other students, as well as during learning the lesson of starter system is more enthusiastic. Then students are more confident and capable enough to understand and demonstrate the content of subjects.